2010
DOI: 10.1109/jsen.2010.2044786
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Physical Modeling of MEMS Energy Harvesting Devices With VHDL-AMS

Abstract: International audienceIn this paper, we propose a VHDL-AMS implementation of a physical model of a microelectromechanical systems (MEMS) piezoelectric microgenerator. Such an executable model acts as a bridge between specifications and fabricated devices. Usually, physical and geometrical parameters of electromechanical parts of a system are only considered in lower levels of the design flow, typically using finite-element tools, which, despite their accuracy, do not allow efficient optimization of the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A further up-to-date example is in F. Gao & Moudni (2010), where a multidomain dynamic proton-exchange-membrane fuel-cell stack model is described and simulated using VHDL-AMS. In (H. Boussetta & Soudani, 2010) a physical model of a microelectromechanical system piezoelectric microgenerator and its controlling circuit is presented and their interaction analyzed. This capability is in fact particularly suitable to accurately represent automotive electro-mechanic components.…”
Section: Vhdl-ams: a Multidisciplinary Language For Multi-resolution mentioning
confidence: 99%
“…A further up-to-date example is in F. Gao & Moudni (2010), where a multidomain dynamic proton-exchange-membrane fuel-cell stack model is described and simulated using VHDL-AMS. In (H. Boussetta & Soudani, 2010) a physical model of a microelectromechanical system piezoelectric microgenerator and its controlling circuit is presented and their interaction analyzed. This capability is in fact particularly suitable to accurately represent automotive electro-mechanic components.…”
Section: Vhdl-ams: a Multidisciplinary Language For Multi-resolution mentioning
confidence: 99%
“…The complexity leads to prohibitive simulation times. Models based on hardware description languages (HDL), such as VHDL-AMS and SystemC-A have recently been proposed [2,3] to accelerate simulation times. However, these solutions have not fully solved the main challenge of the traditional analogue simulation approach based on Newton-Raphson iterations which are the main cause of the long CPU times.…”
Section: Introductionmentioning
confidence: 99%
“…Pending the development of such a solver, in this paper we have used SystemC-A [14], a proprietary extended SystemC which has recently been equipped with an analog solver that uses a linearised state-space equation formulation [15], capable of simulating efficiently intricate operational scenarios of an energy harvester system. Recently, Boussetta et al [16] reported a VHDL-AMS model of a MEMS (microelectromechanical system) piezoelectric microgenerator. Their model incorporates the physical and geometric parameters of the microgenerator, is reusable, reflects experimental results well and can be integrated in global simulation of multidomain and mixed signal systems such as complete wireless sensor nodes.…”
Section: Introductionmentioning
confidence: 99%